Espécies do gênero Physalaemus no Estado do Rio de Janeiro (Amphibia, Anura, Leptodactylidae) - Weber, Luiz Norberto (1998)
This work is about the morphology, reproduction, mating calls, natural history and distribution of seven species of the genus Physalaemus Fitzinger, 1826, from the State of Rio de Janeiro. The morphology of adults and tadpoles are described, as well as characteristics related with the reproductive behavior, including breeding sites; larval development; calling sites; breeding seasons. Some vocalizations are described. Taxonomic and biogeographic notes of the species are discussed and compared with the literature.